Співвідношенння Крамерса–Кроніга – доповнююча “time-domain” спектроскопію методика - Ovechko, V.S. (Publishing house "Academperiodika", 2020)
We have proposed a new method for obtaining the Kramers–Kronig relations based on the analysis of the earlier proposed solution of the wave equation for a dispersion medium [2]. The use of this solution for ultra-wideband (femtosecond) optical signals allowed us to propose a simultaneous measurement method for both n (w) and k (w). The latter is a further development of the time-domain spectroscopy method.